1990
DOI: 10.1002/ajmg.1320360208
|View full text |Cite
|
Sign up to set email alerts
|

Cor pulmonale as a complication of methylmalonic acidemia and homocystinuria (Cb1‐C type)

Abstract: We report an infant with a bronchiolitis-like illness and rapid deterioration who developed a cor pulmonale-like picture with a dilated right ventricle. Urinary organic acid assays established a probable diagnosis of Cbl-C-type methylmalonic aciduria, later confirmed by complementation studies. Despite medical intervention and cyanocobalamin treatment the patient died on his tenth hospital day. Postmortem examination showed the presence of thromboemboli in the pulmonary circulation. We hypothesize that acute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 10 publications
2
46
0
2
Order By: Relevance
“…At least 15 patients with cblC have been reported with cardiomyopathy (Table 1; Baumgartner et al 1979;Brandstetter et al 1990;Carmel et al 1980;Chenel et al 1993;De Bie et al 2009;Longo et al 2005;Geraghty et al 1992;Ogier de Baulny et al 1998;Profitlich et al 2009). However, the specifics regarding the type and echocardiographic manifestations of the cardiac lesions have not been fully delineated.…”
Section: Discussionmentioning
confidence: 99%
“…At least 15 patients with cblC have been reported with cardiomyopathy (Table 1; Baumgartner et al 1979;Brandstetter et al 1990;Carmel et al 1980;Chenel et al 1993;De Bie et al 2009;Longo et al 2005;Geraghty et al 1992;Ogier de Baulny et al 1998;Profitlich et al 2009). However, the specifics regarding the type and echocardiographic manifestations of the cardiac lesions have not been fully delineated.…”
Section: Discussionmentioning
confidence: 99%
“…Familial cases of TMA occur as a result of a genetic deficiency in this protease [Furlan et al, 1998]. Familial TMA is also described in patients with complement deficiencies and in infants with a disorder of vitamin B 12 metabolism cobalamin-C (Cbl-C) [Baumgartner et al, 1979;Brandstetter et al, 1990;Geraghty et al, 1992;Russo et al, 1992;Chenel et al, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…12 Thromboembolic complications have been reported in cblC defect as the result of hyperhomocysteinemia in inducing vascular damage. 13 Brandstetter et al 14 reported an infant with a probable cblC defect, a bronchiolitislike illness, and acute cor pulmonale secondary to pulmonary thromboembolism. However, this patient also showed seizurelike activity and hypotonia.…”
Section: Discussionmentioning
confidence: 99%